Implementasi Aplikasi Web untuk Manajemen Surat Masuk dan Surat Keluar di SMK Negeri 4 - Yuspina Danomira; Gunawan Prayitno (STMIK Pesat Nabire, 2024)
This research aims to develop and implement a web application for incoming and outgoing mail management at SMK Negeri 4. Efficient mail management is a critical aspect of school administration, but it is often constrained by manual systems that are prone to errors and inefficiencies. The development methodology uses the Waterfall model, including the stage of needs analysis, design, implementation, testing, and maintenance. This application is designed with key features including digital record-keeping, archiving, searching, and mail status tracking. The test results show that this application is able to significantly improve the efficiency of mail management, reduce the risk of document loss, and speed up the mail search process. The implementation of this application results in improved school administration performance, with faster mail processing times and higher management accuracy. This research contributes to the modernization of the school administration system and can be a model for similar implementation in other educational institutions.